The role of student support programmes in assisting black students to navigate the institutional culture at the University of Witwatersrand - Mthembu , Mthokozisi (My University, 2022)
Historically White Universities (HWU) have experienced an influx of black students since the demise of Apartheid. Addressing the scarcity of skills and underrepresentation of black people in South Africa’s high skilled professions, this study looks at the country’s higher education system as an underpinning factor to the problem. Black students experience potent challenges in these institutions that impede their academic efforts, the difficulty to integrate into their institutional cultures is ascertained as one of the most potent issues by the literature. As a response to assist students facing such challenges, universities have inaugurated Student Support Programmes (SSP). This issue has also necessitated that academic work probing the ways in which black students engage with the culture of HWU be undertaken. Work in this regard has indeed increased, however not enough has been done to ascertain the utility of SSPs. This study, therefore, undertakes to address this gap, probing the extent to which SSPs assist black engineering students to navigate the institutional culture of the University of Witwatersrand. The aim of this study is to ascertain ways in which SSPs can be recalibrated to render more effective support to black students, helping them navigate the institutional culture of HWU with more success. The study conducted qualitative interviews with 14 students and 6 employees of SSPs. Using Tinto’s model of Institutional Action, the study found it insufficient to conceptualize institutional culture solely based on phenomena occurring within the demarcations where academic learning takes place. The argument of this study, therefore, is that SSPs are valid only to the extent that they deal with issues within the environment where academic learning takes place, they do not address issues that arise from outside of this context. The recommendation made is that SSPs should increase the extent of support they render to students by taking the urban context of the university into account in their design and implementation.
A dissertation submitted in partial fulfilment of the requirements for the degree of MA in Organisational and Institutional Studies, University of the Witwatersrand, 2022